Performance Analysis of OFDM under AWGN and Rayleigh Fading Channels Based on Software Defined Radio - Arum Dimarsasi, Ivana; Saptono, Rachmad; Syirajjudin, Muhammad (Faculty of Engineering, Universitas Brawijaya, 2024)
Orthogonal Frequency Division Multiplexing (OFDM) is a very efficient and popular modulation technique in modern wireless communication systems. OFDM offers advantages in terms of spectrum efficiency, resistance to multi-path interference, and is able to support high data rates. This OFDM system uses the concept of Software Defined Radio (SDR) because it is able to implement directly with the help of USRP B210 hardware. The OFDM system consists of a transmitter and receiver that are processed by digital signal processing to encode, decode, and modulate data. This study uses GNU Radio software as a transmitter and receiver model. The purpose of this study is to compare the performance of real-time data transmission through the AWGN (Additive White Gaussian Noise) and Rayleigh Fading channels. The results of the study show that the performance of the OFDM system built, namely the use of BPSK modulation on the AWGN channel has the best performance with the lowest BER results of 0.376 and SNR 14 dB.